Parental Choice: Facilitators and Barriers of Utilizing Childcare Centers in Karachi, Pakistan - Zahra Premani; Zohra Kurji; Yasmin Mithani (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This qualitative study explored parental perceptions regarding parent's choice of quality childcare centers in urban areas of Karachi, Pakistan. Sixteen participants were selected from two centers in different geographical areas. For parents, the most common reason for selecting the childcare centers was the lack of other available options such as family support. Availability and accessibility of childcare centers were reported as supporting factors, while lack of family support, lack of information, and violent city conditions were identified as barriers to choosing childcare centers. In addition, husband support was perceived as a facilitator and a barrier to choosing childcare centers.